Postdramatic Tendencies in Martin Crimp’s Fewer Emergencies - Çağlayan Doğan (Current Perspectives in Social Sciences, 2024)
Martin Crimp has been one of the most prominent playwrights on the British stage since his first appearance. Although his oeuvre consists of absurdist and postdramatic plays, he translated classic texts such as Cyrano De Bergerac, Rhinoceros, The Seagull and The Misanthrope. Fewer Emergencies is a short play that forms part of Crimp's triptych, which also includes Whole Blue Sky and Face to the Wall. In Fewer Emergencies, Crimp creates a theatrical atmosphere that deconstructs the tenets of conventional dramatic theatre. In the playlet the characterisation is reminiscent of his earlier thought-provoking Attempts on Her Life, which had no obvious character attributions. In Fewer Emergencies he makes a similar kind of characterisation. He simply numbers the characters 1, 2, 3. In this way, Crimp creates an inspiring theatrical space. The aim of this study is to uncover the postdramatic theatricality of Crimp's Fewer Emergencies.